Measurement the level of liquid in a container by using capacitive Probe - Shtaya, Manar; Dwekat, Tahany (My University, 2017)
Measuring the level of liquid in a container is an important process in various process industries . The design of a capacitance transducer using a 555 timer circuit measuring the capacitance in terms of frequency and interfaced to a microcontroller to provide an accurate level measurement system .The importance of our project we have is being able to see the liquid level in the subject of any bowl using a capacitor cylindrical shape , and in order to facilitate the practical applications in various fields of life. There are multiple ways to achieve this result, but we used the capacitor and we build it one way enables us to get accurate results of the height of liquid .